The role of the tumor microenvironment in colorectal cancer and the potential therapeutic approaches. Issue 8 (8th July 2022) - Zafari, Narges; Khosravi, Fatemeh; Rezaee, Zahra; Esfandyari, Sahar; Bahiraei, Mohamad; Bahramy, Afshin; Ferns, Gordon A.; Avan, Amir
Abstract: Background: Colorectal cancer (CRC) with a high prevalence is recognized as the fourth most common cause of cancer‐related death globally. Over the past decade, there has been growing interest in the network of tumor cells, stromal cells, immune cells, blood vessel cells, and fibroblasts that comprise the tumor microenvironment (TME) to identify new therapeutic interventions. Methods: Databases, such as Google Scholar, PubMed, and Scopus, were searched to provide an overview of the recent research progress related to targeting the TME as a novel therapeutic approach. Results: Tumor microenvironment as a result of the cross talk between these cells may result in either advantages or disadvantages in tumor development and metastasis, affecting the signals and responses from the surrounding cells. Whilst chemotherapy has led to an improvement in CRC patients' survival, the metastatic aspect of the disease remains difficult to avoid. Conclusions: The present review emphasizes the structure and function of the TME, alterations in the TME, its role in the incidence and progression of CRC, the effects on tumor development and metastasis, and also the potential of its alterations as therapeutic targets. It should be noted that providing novel studies in this field of research might help us to achieve practical therapeutic strategies based on their interaction. Abstract : Inflammatory pathways play a role in tumor microenvironments and can be considered as therapeutic targets.